The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.7763/ijssh.2015.v5.414
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Transportation System for the Disabled Tourist in the National Park of Johor State, Malaysia

Abstract: Abstract-Tourism is a rapidly growing industry in the Asian and Pacific Region, disabled person and older persons are becoming a growing group of consumers of travel, sports and other leisure-oriented products and services. However, their travel experiences are still characterized by transportation constraints, inaccessible accommodation and tourism sites, and inadequate customer services. Purpose of this paper is to identify the constraints gone through by the disabled tourists in the transportation services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For senior tourists, only three items landed in Area 9 (concentrate here), namely "cleanliness of tourism attractions," "variety of senior-friendly leisure facilities," and "barrier-free facilities of public transportation." In Malaysia, the outdoors, transportation systems, and public buildings are generally not senior-friendly (Sanmargaraja & Ta Wee, 2015). It is thus reasonable that senior tourists allocated these three elements to this area.…”
Section: Ipa Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For senior tourists, only three items landed in Area 9 (concentrate here), namely "cleanliness of tourism attractions," "variety of senior-friendly leisure facilities," and "barrier-free facilities of public transportation." In Malaysia, the outdoors, transportation systems, and public buildings are generally not senior-friendly (Sanmargaraja & Ta Wee, 2015). It is thus reasonable that senior tourists allocated these three elements to this area.…”
Section: Ipa Resultsmentioning
confidence: 99%
“…Nevertheless, concerning senior travel studies in Asia, scholars believe that much remains to be done on seniors' concerns and special care (Mary et al, 2019). Thus, there is an urgent need to analyze senior tourists' preferred attributes of tourism destinations, notably in the case of Malaysia which is soon approaching a third aged population (Sanmargaraja & Ta Wee, 2015). To the best of our knowledge, limited studies have examined senior-friendly destination attributes across two generations, that is, future seniors and seniors, especially in the context of seniors' tourism needs and preferences in Malaysia.…”
Section: Senior-friendly Destination Attractivenessmentioning
confidence: 99%
“…It comprises of (1) assurance on accessibility despite maintenance activity is conducted (2) criticality of facilities maintenance itself, (3) assurance on comfort and safety, (4) reliable medium to ask for assistance or giving feedback, (5) provision of signage that is clearly seen and easily understood and (6) staff responsiveness. Based on prior studies, Kadir and Jamaludin (2013) and Sanmargaraja and Wee (2015a) emphasised that improved services are important apart from excellent design and accessible building. The current study indicates space for improvement on service quality provided for PWDs as it was found that service quality measured is below the satisfaction level.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The implementation of the Persons with Disabilities Act 685 (2008) has driven towards providing protection, rehabilitation, development and well-being of PWDs. Recently, the attention towards PWDs is increasing by the action of accommodating PWDs’ needs in various areas such as education institutions, public transports, national parks, shopping malls, hotels, tourism industry, mosques and public buildings (Bashiti and Abdul Rahim, 2015; Bashiti and Rahim, 2016; Ismail et al , 2015; Ja'afar et al , 2017; Kadir and Jamaludin, 2012; Rahim and Abdullah, 2009; Rahim et al , 2010; Sanmargaraja and Wee, 2011, 2015a, b; Wee and Sanmargaraja, 2015). However, the study on PWDs in hospital building is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Transportation is among the most important stages of travel. Transportation problems in National Parks for disabled people have been researched, which mentioned that the population of disabled people, known as the minority community, is increasing day by day, and the problems experienced by disabled tourists are increasing in parallel [ 60 ]. Soltani and colleagues [ 61 ] emphasized that PWDS experience more difficulties and access problems while traveling and using public transportation.…”
Section: Findings and Discussionmentioning
confidence: 99%